THE PERCEIVED LEVEL OF COMPETENCE BASED ON EXPERIENCE AND GENDER OF THE ADMINISTRATIVE STAFF OF PRIMARY EDUCATION IN GREECE AND THE NEED FOR TRAINING - ANASTASIOU, ADAMOS (Innovare Journal of Education, 2021)
The ideas of ‘competence’ and ‘competencies’ have become central in the last decades in education, as experts have focused their interest on the importance of setting learning objectives in order to help students familiarise themselves with the learning process. In the present study, it is examined whether there is a difference in the perceptions of the administrative staff (both principals and vice-principals) on their level of competence as far as their experience (experienced or novice - inexperienced) and a common personal characteristic, such as their gender (male or female), are concerned. A total of 412 administrative staff that is 261 principals 151 vice-principals responded to a five-point Likert-scale questionnaire. The statistical comparison was performed by applying the 2-factor analysis of variation (ANOVA). This analysis was preceded by check for equality of variance between the respective groups (Levene’s test). Based on the findings concerning experience and gender correlation, it is revealed that the greatest need for training seems to concern novice female primary school administrative staff, while on the contrary, the least need for training concerns the experienced male ones. Training programme designers should take this fact very seriously when creating educational courses.